Clinical findings, surgical treatment and long‐term outcome of dogs and cats with double aortic arch: four cases (2005–2022). (16th August 2022) - Rossanese, M.; Cinti, F.; Chanoit, G. P. A.; Brockman, D. J.
Abstract : Objective: To describe the clinical presentation, diagnostic findings, treatment and long‐term outcome following surgery of dogs and cats undergoing surgical treatment for a double aortic arch. Materials and Methods: Medical records of dogs and cats diagnosed with a double aortic arch between 2005 and 2022 at three small animal referral hospitals were retrospectively reviewed. Long‐term outcome was assessed by a clinical examination and/or by contacting the owners or referring veterinarians. Results: Two dogs and two cats were included. Regurgitation after eating, stunted growth and poor weight gain were the predominant clinical features. All animals had thoracic radiography and oesophagography; a dilation of the cranial thoracic oesophagus cranial to the heart base, was described in all animals. CT angiography confirmed double aortic arch in three of these and the right aortic arch was larger and appeared more well developed compared with the left aortic arch in all based on CT or surgical findings. Surgery was performed via a left fourth intercostal thoracotomy; ligation and transection of the lesser left aortic arch was performed. Follow‐up time ranged from 360 to 1563 days. All animals showed a marked improvement during the postoperative period, and all gained weight gradually. Owners' perception of the surgical procedure outcome and quality of life was described as excellent for all animals. Clinical Significance: Surgical ligation of the lesser aortic arch in dogs and cats with double aortic arch is associated with a favourable prognosis for recovery, resolution of clinical signs, and quality of life with only minor feeding modifications.